A complicated man : the life of Bill Clinton as told by those who know him - Takiff, Michael, 1955- (Yale University Press, 2010)
Though Bill Clinton has been out of office since 2001, public fascination with him continues unabated. Many books about Clinton have been published in recent years, but no single-volume biography covers the full scope of Clinton's life from the cradle to the present day; and books on Clinton have tended to be highly polarized, casting the former president in an overly positive or negative light. In this, the first complete oral history of Clinton's life, historian Michael Takiff presents the first truly balanced book on one of our nation's most controversial and fascinating presidents. Through more than 150 chronologically arranged interviews with key figures including Bob Dole, James Carville, and Tom Brokaw, among many others, this book goes far beyond the well-worn party-line territory to capture the larger-than-life essence of Clinton the man.--From publisher description.